POTENTIAL OF ETHANOL EXTRACT OF TURMERIC LEAVES (Curcuma longa) ON THE REDUCTION OF CHOLESTEROL LEVELS IN MICE (Mus musculus) HYPERCHOLESTEROLEMIA MODEL - Putri Yoggy Mayssa Kisdiati; Khoirul Ngibad (Universitas Negeri Yogyakarta, 2025)
Tests on the dosage and effectiveness of turmeric leaf ethanol extract in lowering cholesterol levels in animal models have never been conducted to explore its therapeutic potential. This study aims to determine the effect of turmeric leaf ethanol extract (Curcuma longa) in reducing hypercholesterolemia levels in mice. This study employed an experimental design, dividing 36 mice into six treatment groups. The treatment group consisted of a negative control, a positive control, a drug control, and three doses of turmeric leaf ethanol extract (14 mg/20 g body weight, 28 mg/20 g body weight, and 56 mg/20 g body weight). Cholesterol levels were measured using a spectrophotometer, and the results were analyzed with the ANOVA test. The results showed a significance value of 0.000, indicating a significant difference in the reduction of cholesterol levels between treatment groups (p < 0.05). Turmeric leaf ethanol extract at a dose of 56 mg/20 g body weight resulted in a reduction of 33.6 mg/dL in mouse cholesterol levels, which is higher than that observed with other doses. Turmeric leaf ethanol extract can lower cholesterol levels in mice, with a dose of 56 mg/20 g body weight providing the most significant reduction. This study demonstrates that turmeric leaf ethanol extract has the potential to serve as a natural therapeutic alternative for managing hypercholesterolemia.